Освітня реформа в Чернігівській губернії: виникнення та функціонування нових навчальних закладів 1804–1819 рр. (держава – спільнота – освіта) - Маслійчук, В. (Сiверянський лiтопис, 2017)
Відкриття та початки функціонування світських навчальних закладів мають
вагоме соціальне наповнення та регіональні особливості. Велика заслуга на цьому полі
діяльності належить директору училищ Чернігівської губернії Михайлу Маркову. На
рівні повітів вдалося зберегти, перетворити і відкрити 10 повітових навчальних закладів (Погар, Ніжин, Стародуб, Глухів, Конотоп, Кролевець, Городня, Остер, Сосниця,
Козелець). Загалом певний успіх з відкриттям повітових училищ з 1811 р. відбувся
завдяки діяльності «почесних смотрителів» (представників місцевого дворянства) у
повітах. Визначальними для заснування і відкриття нових навчальних закладів були
не освітні комунікації, а персональні взаємини. Открытие и начало функционирования светских учебных заведений включают в
себя существенный социальный контекст и имеют региональные особенности. Огромная заслуга на этом поле деятельности принадлежит директору училищ Черниговской
губернии Михаилу Маркову. На уровне уездов удалось сохранить, трансформировать
и открыть 10 уездных учебных заведений (Погар, Нежин, Стародуб, Глухов, Конотоп,
Кролевец, Городня, Остер, Сосница, Козелец). Определенный успех с открытием уездных
училищ с 1811 г. был связан с деятельностью почетных смотрителей (представителей
местного дворянства) в уездах. Определяющими для основания и открытия новых
учебных заведений были не образовательные коммуникации, а персональные отношения. The opening and the beginnings of a functioning secular educational institutions have a
strong social content and regional features. Establishment, conservation, transformation of
schools in Chernihiv province were related to the opening of the Kharkov University 1805 . Great merit in this field of activity belongs to the Director of the schools of the Chernihiv
province Mikhaylo Markov.
Despite the opening of the Chernihiv gymnasium with a district school of 1805, the first
attempts of opening elementary schools were not always successful. At the level of counties
cannot save, convert and open 10 discrict schools (Pohar, Nizhyn, Starodub, Glukhiv, Konotop,
Krolevets, Horodnia, Oster, Sosnytsia, Kozelets). Separately, outside of these initiatives worth
Novgorod-Siversk` Gymnasium of 1808, a district school, and Nizhyn`s Greek Oleksander`s
school. Elementary schools functioned only 2-3. In General, some success with the opening of
County schools was due to the activity of the «pochesny smotritelì» (representatives of local
nobility) in the counties.
Crucial to the establishment and opening of new schools were not educational communication
but personal relationships. Low status of the teachers ‘ work, sort of a noblemen’s support for
corporations, focused not on personnel or high quality problems but on the material, limited access
to education have played a major role in the further development of educational structures.